Plant Genetic Recourses. EUCARPIA 19 - A.S. Domblides; E.A. Domblides; V.A. Kharchenko (Овощи России, 2009)
The brief essay covers the topic subjects of Eucarpia 19 on Genetic Recourses 2009, 26th - 29th May. The challenging tasks and current trends toward exploration of Plant Genetic Resources are summarized in the article.